The development and evaluation of a custom-built synchronous online learning environment for tertiary education in South Africa - Halse, Michelle Louise (Rhodes University, Faculty of Science, Department of Computer Science, 2008)
The Departments of Computer Science and Information Systems at Rhodes University currently share certain honours-level (fourth year) course modules with students from the corresponding departments at the previously disadvantaged University of Fort Hare. These lectures are currently delivered using video-conferencing. This was found to present a number of problems including challenges in terms of implementing desired pedagogical approaches, inequitable learning experiences, student disengagement at the remote venue, and inflexibility of the video-conferencing system. In order to address these problems, various e-learning modes were investigated and synchronous e-learning were found to offer a number of advantages over asynchronous e-learning. Live Virtual Classrooms (LVCs) were identified as synchronous e-learning tools that support the pedagogical principles important to the two universities and to the broader context of South African tertiary education, and commercial LVC applications were investigated and evaluated. Informed by the results of this investigation a small, simple LVC was designed, developed and customised for use in a predominantly academic sphere and deployment in a South African tertiary educational context. Testing and evaluation of this solution was carried out and the results analysed in terms of the LVC's technical merits and the pedagogical value of the solution as experienced by students and lecturers/facilitators. An evaluation of this solution indicated that the LVC solves a number of the identified problems with video-conferencing and also provides a flexible/customisable/extensible solution that supports highly interactive, collaborative, learner-centred education. The custom LVC solution could be easily adapted to the specific needs of any tertiary educational institute in the country, and results may benefit other tertiary educational institutions involved in or dependant on distance learning.
Keywords: Education, Higher -- South Africa -- Computer-assisted instruction; Universities and colleges -- Computer networks -- South Africa; Internet in higher education -- South Africa; Distance education -- South Africa -- Computer-assisted instruction; Computer-assisted instruction -- South Africa; Computer science -- Study and teaching (Higher) -- South Africa